Anticipatory scene representation in preschool children's recall and recognition memory. Issue 5 (1st September 2016) - Kreindel, Erica; Intraub, Helene
Abstract: Behavioral and neuroscience research on boundary extension (false memory beyond the edges of a view of a scene) has provided new insights into the constructive nature of scene representation, and motivates questions about development. Early research with children (as young as 6–7 years) was consistent with boundary extension, but relied on an analysis of spatial errors in drawings which are open to alternative explanations (e.g. drawing ability). Experiment 1 replicated and extended prior drawing results with 4–5‐year‐olds and adults. In Experiment 2, a new, forced‐choice immediate recognition memory test was implemented with the same children. On each trial, a card (photograph of a simple scene) was immediately replaced by a test card (identical view and either a closer or more wide‐angle view) and participants indicated which one matched the original view. Error patterns supported boundary extension; identical photographs were more frequently rejected when the closer view was the original view, than vice versa. This asymmetry was not attributable to a selection bias (guessing tasks; Experiments 3–5). In Experiment 4, working memory load was increased by presenting more expansive views of more complex scenes. Again, children exhibited boundary extension, but now adults did not, unless stimulus duration was reduced to 5 s (limiting time to implement strategies; Experiment 5). We propose that like adults, children interpret photographs as views of places in the world; they extrapolate the anticipated continuation of the scene beyond the view and misattribute it to having been seen. Developmental differences in source attribution decision processes provide an explanation for the age‐related differences observed. Abstract : Children (4–5 years old) and adults misremembered photographs (simple, single‐object scenes) as showing more of the world than they'd actually seen (boundary extension), as measured by recall (drawing) and recognition memory (forced‐choice) tasks. Recognition responses were asymmetrical, with wider‐angle foils drawing more errors than close‐up foils; however, when in another experiment more complex scenes (very wide‐angle views) were presented, now only children exhibited this anticipatory spatial error, unless adults' stimulus duration was greatly reduced. We suggest that greater boundary extension for children reflects developmental differences in source monitoring; with children being less adept at distinguishing self‐generated from visually‐perceived information in memory.